Review Artikel: Pengaruh Perbandingan Fase Gerak Dalam Analisis Senyawa Hidrokuinon Pada Sediaan Kosmetik Menggunakan Metode High Performance Liquid Chromatography (HPLC) - Basmalah, Nur; Hariadi , Nayla Nur Azkia; Mulki , Munir Alinu (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Hydroquinone is a compound that is often used in cosmetic products because of its ability to brighten the skin by inhibiting melanin production. However, its use can cause dangerous side effects such as irritation, hyperpigmentation and the risk of cancer, so its use in cosmetics has been limited by BPOM. High Performance Liquid Chromatography (HPLC) is an analytical method commonly used to detect hydroquinone in cosmetic preparations because of its sensitivity and ability to separate compounds with high complexity. This article is a literature review which aims to determine the effect of mobile phase comparison on hydroquinone analysis using the HPLC method. The research results show that selecting the right mobile phase is very important to guarantee accurate, precise and efficient analysis results. The combination of a polarity-based mobile phase that matches the properties of hydroquinone provides good resolution, high sensitivity, and optimal retention time. This research is expected to provide guidance in optimizing the HPLC method for hydroquinone analysis, and is expected to support cosmetic safety monitoring.